Experimental Application of Semi-Quantitative Methods for the Assessment of Occupational Exposure to Hazardous Chemicals in Research Laboratories - Mastrantonio R; Scatigna M; D'Abramo M; Martinez V; Paoletti A; Fabiani L (Risk Management and Healthcare Policy, 2020)
Riccardo Mastrantonio,1 Maria Scatigna,1 Marco D’Abramo,2 Viviana Martinez,3 Antonio Paoletti,1 Leila Fabiani1 1Department of Life, Health & Environmental Sciences, University of L’Aquila, L’Aquila, Italy; 2Freelance Health and Safety Technician, Frosinone, Italy; 3Abruzzo e Molise Interregional Transplant Coordination Centre, ASL1 Abruzzo, L’Aquila, ItalyCorrespondence: Riccardo Mastrantonio Email riccardomastrantonio@yahoo.itPurpose: The aim of this study was to evaluate the application of some chemical risk assessment semi-quantitative methods and also to identify potential bias or differences originated by applying different methods to the same activities.Methods: We collected the data related to the chemical agents used in three different activities of three laboratories of an Italian university; the methods we compared were: MoVaRisCh, COSHH Essentials, LaboRisCh and Datarisch.Results: The input parameters requested by each method are shown for each activity and for each used chemical. We collected the results obtained since the application of the four different tools in three tables. The use of some chemicals (especially of the activity n° three) shows a not irrelevant risk for the users.Conclusion: Our findings show that COSHH Essentials, MoVaRisCh and Datarisch tools are consistent in the identification of a risk level; the small differences are related to risk rating, to be considered in relation with the specific structure of the method applied. The differences detected in the risk rating may be overcome by applying, for each working activity we want to assess, two or more different semi-quantitative tools. This strategy can allow to reduce the exposure to chemicals of the workers.Keywords: chemical risk, work exposure, chemical exposure, construction industry